Development of Catalysts for Abating Toxic Nitrogen Oxides in Gas Emissions of Nitrogen Acid Production - Soloviev, S.O.; Kyriienko, P.I.; Popovych, N.O.; Larina, O.V. (Science and Innovation, 2024)
Introduction. Reducing nitrogen oxides (NOx) emissions from industrial plant is one of the most important environmental issues. Selective catalytic reduction (SCR) of NOx is the main way to neutralize NOx emissions, the effectiveness of which is determined by the activity of catalysts that need to be improved. Problem Statement. SCR NOx with ammonia using alumina-vanadic catalyst (AVC-10) is the main method for neutralizing toxic NOx in gas emissions from nitrogen industry plants. However, this catalyst contains toxic vanadium and does not meet present-day requirements for degree of purification from NOx and decomposition of residual NH3. Therefore, it is very important to develop and to implement a technology for manufacturing vanadium-free catalysts to neutralize NOx in gas emissions and for their further use in industry, which will help improve the environment condition. Purpose. To develop and to implement technology fundamentals for producing a highly active alumina-copper-zinc catalyst for SCR NOx with ammonia to neutralize NOx emissions in nitric acid production. Materials and Methods. Aluminum-copper-zinc catalysts are prepared by impregnating γ-Al2O3 granules (grade A-1) with solutions of copper and zinc nitrates. The activity of catalysts is determined in a flow-bed reactor equipped with a gas analyzer. Results. A technology for preparation of nanophase alumina-copper-zinc catalysts with a "crust" structure of the active layer for selective reduction of nitrogen oxides in gas emissions of nitric acid production has been developed. The technology ensures the localization of copper oxide in the surface layer of carrier granules, which causes a high activity of catalysts based on this technology as compared with conventional catalysts. Conclusion. The technological process of designed catalyst production has been worked out under conditions of Katalizator Additional Liability Company, Kamianske (Dnipro Oblast). Tests carried out using a pilot plant at operating unit for non-concentrated nitric acid production at Ostchem have showed that the designed catalyst ensures reducing the amount of residual nitrogen oxides in purified gas down to 0.001-0.002% vol. and removing almost all ammonia from the gas.